Numerical study of the influence of the parameters of statistical distribution of the structural elements’ ultimate strength on deformable bodies’ fracture processes (Fracture and Structural Integrity, 2024)
This work is dedicated to the numerical study of the influence of the parameters of statistical distribution of the structural elements’ ultimate strength on fracture processes of deformable bodies with stress concentrators. The loading diagrams, the macro level behavior and the damaging process kinetics have been studied using various probability distribution laws and their standard deviations. The main types of the damage accumulation process have been identified. The approach basing on the analysis of the solutions of the boundary value problems within the elasticity theory has been proposed in order to predict the fracture process kinetics, the corresponding parameters have been introduced. Advantages, limitations and potential practical use of the proposed methodology have been discussed. It has been concluded that the statistical distribution of the structural elements’ strength properties should be taken into account in the numerical modeling of the fracture processes to ensure the reliability and safety of critical structures.
Keywords: Fracture; Finite element method; Numerical modeling; Brittle body; Strength properties distribution